READINESS OF ARTIFICIAL INTELLIGENCE TO ACCELERATE BUREAUCRATIC REFORM IN INDONESIA (Universitas 17 Agustus 1945 Surabaya, 2021)
The national use of AI in the government sector is necessary to achieve effectiveness and efficiency in supporting bureaucratic reform and policy decision making in order to implement good governance. The research uses qualitative descriptive methods by reviewing previous research, and reviewing policies related to the use of AI in government and bureaucratic reform. The results show that in terms of governance, AI systems do not yet have specific laws governing and ensuring the security and protection of citizen data and the use of algorithms against the misuse of electronic transactions. In terms of governance, AI development is needed as an effort to maintain public trust and government legitimacy. In terms of infrastructure Indonesia is still constrained by the creation of data that is very difficult and does not allow for reuse. In terms of skills and education, the digital skills of workers in Indonesia are still middle level. In terms of government and public services, Indonesia still has to continue to increase the availability of public services digitally. In order to improve the management of AI Indonesia builds artificial intelligence industry research and innovation collaboration (KORI-KA), a quadruple-helix approach between government, industry, academia and the community. At a strategic level, AI management is conducted with policy, accountability, and accountability approaches. At the operational level, cybersecurity against data includes infrastructure security and the use of anonymous data methods to keep data owners unidentified.